2009
DOI: 10.1007/s10584-009-9571-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of climate change on durum wheat cropping in Tunisia

Abstract: The potential effect of climate change on durum wheat in Tunisia is assessed using a simple crop simulation model and a climate projection for the 2071-2100 period, obtained from the Météo-France ARPEGE-Climate atmospheric model run under the IPCC (International Panel on Climate Change) scenario A1B. In the process-oriented crop model, phenology is estimated through thermal time. Water balance is calculated on a daily basis by means of a simple modelling of actual evapotranspiration involving reference evapotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 20 publications
(17 reference statements)
1
30
0
1
Order By: Relevance
“…Without clearly disentangling the predominant role of the length of the growing period (t1 − t0 + t2) or the intensity of the dry season WSI, as both variables were correlated to the same autumnal rainfall amount, we could show that both variables did not exert any significant trend over the recent period in allowing for the ecosystem sustainability. Actually, we observed that the start of the drought period (t1) was significantly earlier in the last decades in the region, as a result of this decreasing winter precipitation (P_ON) as previously observed in the region [87], so that both the length of growing period and the drought period should be affected. However, we also showed that the start of the growing season (t0) also moved toward an earlier start date as a consequence of warmer winter temperatures, compensating for the earlier (t1) and leading to constant (t1 − t0) growth period, a result recently pointed out for Quercus ilex in southern France [88].…”
Section: Quercus Suber Vulnerability To Recent Climate Changes Under supporting
confidence: 77%
“…Without clearly disentangling the predominant role of the length of the growing period (t1 − t0 + t2) or the intensity of the dry season WSI, as both variables were correlated to the same autumnal rainfall amount, we could show that both variables did not exert any significant trend over the recent period in allowing for the ecosystem sustainability. Actually, we observed that the start of the drought period (t1) was significantly earlier in the last decades in the region, as a result of this decreasing winter precipitation (P_ON) as previously observed in the region [87], so that both the length of growing period and the drought period should be affected. However, we also showed that the start of the growing season (t0) also moved toward an earlier start date as a consequence of warmer winter temperatures, compensating for the earlier (t1) and leading to constant (t1 − t0) growth period, a result recently pointed out for Quercus ilex in southern France [88].…”
Section: Quercus Suber Vulnerability To Recent Climate Changes Under supporting
confidence: 77%
“…This approach has been widely adopted to simulate relative yields of crops growing under water stress conditions. The generic process-oriented model is designed with an agro-meteorological perspective to be used at regional scales, accounting for the development, soil water balance and yields of selected crops (Lhomme, Mougou, and Mansour 2009 …”
Section: Drought Analysis In Syriamentioning
confidence: 99%
“…Given that systematic errors preclude the direct use of climate model outputs, future data were obtained on a daily basis using the "climate anomalies" method (Déqué, 2007 ;Wilby et al, 2009). Additive or multiplicative change factors, calculated on a monthly basis, were applied to the observed daily weather data to generate the future data, as detailed in Lhomme et al (2009).…”
Section: Past and Future Climate Datamentioning
confidence: 99%